KONTESTASI GELAR ADAT “SUTTAN” DALAM PANGGUNG POLITIK LAMPUNG - Annissa Valentina (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2018)
This article examines the shifting of the meaning of the title of adat where thereis a dualism of the function of the title of adat when traditional leaders enter the political world or vice versa, politicians who get customary titles. The highest customary titles such as